Peningkatan Hasil Belajar IPA Materi Siklus Air Melalui Media DoSiAr Pada Peserta Didik Kelas V SDN 5 No. 050728 Tanjung Pura - Enda Lovita Pandiangan; Fahrunnisa; Fitri Ramadani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
The issue of poor scientific learning results, particularly for the water cycle curriculum, is the main emphasis of this study's class V pupils at SDN 5 No. 050728 Tanjung Pura. By employing DoSiAr media, this project seeks to enhance students' learning outcomes in scientific classes concerning the water cycle. Using the Classroom Action Research (PTK) technique, which comprises of two cycles, the research was carried out in class V at SDN 5 No. 050728 Tanjung Pura. Records, exams, and observation sheets were used to gather research data. Utilizing DoSiAr media, the study's findings demonstrated a statistically significant improvement in learning from cycle I to cycle II. Two meetings are held throughout each of the two cycles that make up this study. According to study findings, learning